Domestic cats’ effect on urban wildlife : using citizen science and camera traps - Johansson, Kajsa (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2021)
Europe has transformed from areas dominated by agricultural and rural to gradually becoming urban communities. With the development in urban and suburban areas, more non-native species have increased, especially domestic species, about 25% of all Swedish households obtain one or more cats. Domestic cats (Felis catus) have contributed to extinction and endangerment of several species of birds, mammals, and reptiles, and constitute a risk for species that are endangered or threatened worldwide. However, the high density of domestic cats in urban areas indicates higher predation on wildlife compared to rural areas with lower densities of domestic cats. Several earlier studies around the world have found evidence that the domestic cat has a negative effect on wildlife, especially avian species. In Sweden, very few studies have been done in the subject on wildlife and its correlation to housing density and domestic cat visitation frequency. This thesis aims to investigate if there is a correlation between wildlife visitation frequency, domestic cats and housing density, using citizen science and camera traps. The data were collected in Umeå municipality, northern Sweden and the analysis was tested on five wildlife species and one species groups using a generalised linear mixed model and divided the domestic cat’s visitation frequency into two categories high or low, testing for a nonlinear correlation. I found more Eurasian magpies in locations with a low visitation frequency of domestic cats. In contrast to my expectation, songbirds as a species group showed the opposite pattern, being more common in locations with more cats. The results also show a positive correlation with housing density for both domestic cats and Eurasian magpies. By knowing how the different species explore or avoid areas where the domestic cat has higher visitation frequency can give support when planning to urbanise new areas, and before creating more suburban areas have an insight on the wildlife living there and with the domestic cat is coming to affect wildlife species if domestic cats get a high abundance in that area.